Mr. Tennent's speech, on the dissenting petition : delivered in the House of Assembly, Charles-town, South-Carolina, Jan. 11, 1777 - Tennent, William, 1740-1777 (Printed by Peter Timothy, 1777)
January 11, 1777 Speech given by William Tennent before the South Carolina House of Assembly. In support of a dissenting petition, the Rev. Tennant argued against religious establishment (of the Church of England), as an infringement of religious liberty. Specifically, he pointed to the unequal privileges enjoyed by the favored establishments.